MANAJEMEN TALENTA GURU GENERASI MILENIAL: PENGARUH PENGEMBANGAN PROFESIONAL BERKELANJUTAN TERHADAP RETENSI DAN KINERJA PENGAJARAN - Abdul Aziz; Wuri Sari Damayanti (CV JK Riset Publishing Group, 2026)
The high turnover rate of millennial teachers poses a critical challenge for school management systems in Indonesia. Schools frequently lose young, talented teachers before they reach their productive peak due to inadequate professional development pathways and unclear career progression structures. This study aims to examine how continuous professional development programs influence the retention and teaching performance of millennial teachers in Indonesian secondary schools. Using a qualitative approach with multiple case study design, data were collected from twelve millennial teachers, six school principals, and four human resource coordinators across four schools in South Sumatra Province through in-depth interviews, observation, and document analysis. Findings reveal that structured mentoring, collaborative learning communities, and transparent career ladders significantly enhance both retention commitment and classroom performance. It is concluded that talent management integrated with continuous professional development is essential for sustaining teaching quality and institutional growth in the era of educational transformation.